Legal Review of Grants from Inheritance to Adopted Children - Sesniati, Avivah; Yumarni, Ani; Lukmanul Hakin, Aal (Magister Kenotariatan Universitas Pasundan, 2024)
Grants to adopted children often cause disputes, especially when the grantor has passed away. Grant disputes arise because there are heirs who feel aggrieved by the existence of the grant, especially grants given to adopted children that exceed the provisions. This study aims to determine and analyze the implementation of grants to inherited property for adopted children based on Article 1666 of the Civil Code and to determine and analyze the obstacles faced in the implementation of grants to inherited property for adopted children. The method used in this research is normative juridical. Namely, the Law is conceptualized as norms, rules, principles, or dogmas. The normative juridical approach is also known as doctrinal approach/research or normative legal research. The normative juridical research stage uses literature studies (review of the literature), but as long as necessary, interviews can be conducted to complement literature studies. The study results found that the implementation of grants to inherited property for adopted children based on Article 1666 of the Civil Code is known that the right to inherit adopted children is not regulated in the Civil Code. Still, specifically for Indonesian citizens of Chinese descent, the position of adopted children is the same as legal children. For this reason, he is entitled to inherit the inheritance of his adoptive parents according to the Law or inherit based on Testamentary inheritance law if he gets a testament (Grant of Wasiat).